Ultrasound-Guided Thoracic Paravertebral Blockade: A Retrospective Study of the Incidence of Complications. (April 2016) - Pace, Meredith M.; Sharma, Balram; Anderson-Dam, John; Fleischmann, Katherine; Warren, Lisa; Stefanovich, Peter
Abstract : BACKGROUND: The benefits of thoracic paravertebral block (TPVB) have been demonstrated for patients undergoing surgery for breast cancer. However, pleural puncture resulting in pneumothorax is a serious complication associated with traditional approaches using guidance from anatomic landmarks and nerve stimulation and may contribute to the low utilization of this block. An ultrasound-guided technique has the potential to reduce complications by providing direct visualization of the paravertebral space during needle manipulation. We evaluated the complications using a single-injection, transverse, in-plane ultrasound-guided technique for paravertebral blockade in patients undergoing mastectomy with immediate reconstruction for breast cancer treatment or prophylaxis. METHODS: Data from all patients who underwent TPVB between January 1, 2010, and December 3, 2013, at Massachusetts General Hospital was prospectively recorded in a computerized database. All blocks were placed for postoperative analgesia after unilateral or bilateral mastectomy with immediate breast reconstruction. Medical records were retrospectively reviewed for any patient who developed complications including accidental pleural puncture, symptomatic pneumothorax, hypotension, or bradycardia, as well as signs and symptoms of toxicity or effects of local anesthetic outside of the paravertebral space. RESULTS: Eight hundred fifty-six patients underwent a total of 1427 thoracic paravertebral injections (285 unilateral and 571 bilateral TPVB). There were 6 complications (0.70%; 99.2% confidence interval, 0.17%–1.86%) including symptomatic bradycardia and hypotension ( n = 3), vasovagal episode ( n = 1), and evidence of possible local anesthetic toxicity ( n = 2). There was no incidence of suspected accidental pleural puncture or symptomatic pneumothorax identified in our study population. CONCLUSIONS: The routine use of a single-injection, transverse, in-plane ultrasound-guided technique for TPVB in patients undergoing mastectomy with immediate breast reconstruction is associated with very few complications. Abstract : Published ahead of print January 11, 2016